Testing association of rare genetic variants with resistance to three common antiseizure medications - Wolking,S; Moreau,C; Nies,AT; Schaeffeler,E; McCormack,M; Auce,P; Avbersek,A; Becker,F; Krenn,M; Møller,RS; Nikanorova,M; Weber,YG; et al. (Epilepsia, 2020)
OBJECTIVE: Drug resistance is a major concern in the treatment of individuals with epilepsy. No genetic markers for resistance to individual antiseizure medication (ASM) have yet been identified. We aimed to identify the role of rare genetic variants in drug resistance for three common ASMs: levetiracetam (LEV), lamotrigine (LTG), and valproic acid (VPA). METHODS: A cohort of 1622 individuals of European descent with epilepsy was deeply phenotyped and underwent whole exome sequencing (WES), comprising 575 taking LEV, 826 LTG, and 782 VPA. We performed gene- and gene set-based collapsing analyses comparing responders and nonresponders to the three drugs to determine the burden of different categories of rare genetic variants. RESULTS: We observed a marginally significant enrichment of rare missense, truncating, and splice region variants in individuals who were resistant to VPA compared to VPA responders for genes involved in VPA pharmacokinetics. We also found a borderline significant enrichment of truncating and splice region variants in the synaptic vesicle glycoprotein (SV2) gene family in nonresponders compared to responders to LEV. We did not see any significant enrichment using a gene-based approach. SIGNIFICANCE: In our pharmacogenetic study, we identified a slightly increased burden of damaging variants in gene groups related to drug kinetics or targeting in individuals presenting with drug resistance to VPA or LEV. Such variants could thus determine a genetic contribution to drug resistance.